Convenient and mild protocol for preparation of α –trimethylsilyloxyphosphonates using sulfamic acid and their oxidation to α – ketophosphonates in the presence of N-bromosuccinimide - Mitragotri, Satish; Kulkarni, Makarand; Desai, Uday; Wadagaonkar, Prakash (Arkivoc, 2021)
A convenient and mild protocol was developed for the trimethylsilylation of α-hydroxyphosphonates using hexamethyldisilazane as the silylating agent in the presence of sulfamic acid (SA) as a heterogeneous solid acid catalyst in dichloromethane as the reaction medium. The utility of SA as the catalyst for deprotection of α-trimethylsilyloxyphosphonates to parent α-hydroxyphosphonates by making a switch to a protic solvent such as methanol was also demonstrated. Furthermore, the oxidation of α–trimethylsilyloxyphosphonates to corresponding α–ketophosphonates was achieved in excellent yields employing N-bromosuccinimide in the presence of catalytic quantity of AIBN.